Advances in the Diels-Alder Reaction in Self-Healing Polymeric Materials - Ren, Junyu (MATEC web of conferences, 2023)
Polymeric functional materials are widely used in all aspects of everyday life. However, they are subject to a variety of environmental influences such as chemical attack, mechanical abrasion or impact and thermal decomposition, resulting in a significant shortening of the service life of polymer materials. Using traditional repair methods, the damaged part of the material is only reattached or reinforced at a macro level. Currently, more and more research is focused on smart composite materials with self-healing properties. This eliminates hidden problems in the use of the material, thereby extending its service life and broadening the range of applications. The Diels-Alder (DA) reaction is a [4+2] cycloaddition reaction between a conjugated diene and a substituted alkene. It has become a hot research topic in the field of self-healing due to its mild reaction conditions and lack of catalyst. In this paper, the progress of research on self-healing polymeric materials is reviewed with a focus on applications in DA reactions. The research progress in this field is reviewed based on the chemical structures of the prepared DA reaction-based polymers, and the development of DA reaction based self-healing polymers is investigated. Finally, the development of selfhealing polymers based on DA reactions is given as an outlook.